Olympic Geography and the Austro-Hungarian Empire (1889-1920) - Bukta, Zsuzsanna (Πανεπιστήμιο Πελοποννήσου, 2025)
The thesis provides a comprehensive overview of the Hungarian Olympic Movement between 1889 and 1920, with an equal emphasis on the other two great nations of the Austro-Hungarian Monarchy, Austria and Czechia, the conflicts between the nations and the work of the three Hungarian IOC members of that period, Ferenc Kemény, Gyula Muzsa and Géza Andrássy. After outlining the political background of the Austro-Hungarian Monarchy, with particular emphasis on nationality issues, the beginnings of the Olympic Movement in Austria and Czechia is described. The activities of the Czech Jiři Guth are highlighted, as his involvement will help to understand de Coubertin's co-opting policy to the IOC and the choice of Ferenc Kemény, the Hungarian founding member of the IOC. The Hungarian physical activities, modern sport movement and the Olympic Movement is detailed, with special focus on the life and activities of Ferenc Kemény. Hungary’s attendance of the inaugural congress in 1894 is described, as well as the endeavours to establish the first committee for the participation at the Olympic Games in Athens. An interesting, but rather forgotten chapter of Olympic history, the possibility of moving the first Games to Budapest is discussed. The events in the Hungarian Olympic Movement between 1896 and 1907 focuses on Kemény’s international activities and the circumstances of his resignation. Through the life and endeavours of Kemény’s successors, Muzsa and Andrássy, the Olympic participation of Hungary in 1908 and 1912, the IOC Congress of Budapest in 1911, and the constant lobby for bringing the Games to Budapest are discussed, as well as the consequences of World War I on Hungary’s Olympic Movement. The method of the research was the analysis of contemporary documents, letters, newspaper articles and secondary sources on the topic.
Keywords: Ολυμπιακοί αγώνες - Ιστορία - Ουγγαρία; Ολυμπιακοί αγώνες - Ιστορία - Τσεχία; Ολυμπιακοί αγώνες - Ιστορία - Αυστρία; Ολυμπιακό κίνημα - Ιστορία - Ουγγαρία; Ολυμπιακό κίνημα - Ιστορία - Τσεχία; Ολυμπιακό κίνημα - Ιστορία - Αυστρία; Olympics - History - Hungary; Olympics - History - Czechia; Olympics - History - Austria; Olympic movement - History - Hungary; Olympic movement - History - Czechia; Olympic movement - History - Austria; Austro-Hungarian Monarchy; Ferenc Kemény; Gyula Muzsa; International Olympic Committee; Sports Diplomacy